Evaluación de medidas para reducir la transmisión de COVID-19 en espacios cerrados, Tegucigalpa, Honduras - Milena Videa Galo; Nora Rodríguez Corea (Revista Médica Hondureña, 2023)
Background. Given the evidence establishing airborne transmission of SARS-CoV-2, it is essential to seek new ways to reduce transmission. Monitoring through carbon dioxide (CO2) meters allows determining indoor air quality. Objective:Assess CO2 levels and use of safety measures to reduce COVID-19 transmission in university classrooms, Tegucigalpa, Honduras, April-May 2022. Methods: Cross-sectional descriptive observational study on classrooms and university students. Data were obtained by observation, measurement and documentation. The sample was by convenience. CO2 concentrations were measured in 5 classrooms using an ARANET4 infrared meter. The biosafety measures used were recorded. Univariate analysis was performed by means of frequency and measures of central tendency; Pearson correlation coefficients and p-values were calculated. Results: Of the 86 participants, 91.9% (79) applied biosafety measures. The maximum CO2 levels found in 5 classrooms were at the recommended level for classrooms (Indoor Air Quality IDA classification, Subdirección de Salud Pública, Madrid, Spain). Discussion: CO2 levels in the classrooms rose with the presence of students. However, the levels achieved do not suggest a risk. Honduras does not have air quality standards for the protection of health from the impacts of atmospheric pollutants. It is necessary to conduct studies with larger sample sizes in terms of sites and participants.